THE ROLE AND IMPORTANCE OF EDUCATION IN FORMING A TRAFFIC CULTURE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article extensively covers the role and importance of education in forming a traffic culture. Today, the issues of ensuring traffic safety, forming a traffic culture in the minds of the younger generation, and developing skills in the correct use of vehicles are of urgent importance. Effective forms of teaching traffic rules in the educational process, pedagogical and psychological approaches are analyzed. Also, practical proposals are put forward for the development of traffic culture in preschool educational institutions, general education schools and the higher education system.